Stionic Influence of Grape Cultivar Syrah (Vitis vinifera L.) on Inter-specific Hybrid Rootstocks - Nitin, P.S.; Patel, V.B.; Singh, S.K.; Verma, M.K.; Mishra, G.P.; Anil, Dahuja; Puneeth, P.V. (South African Journal of Enology and Viticulture, 2025)
Rootstocks play a crucial role in commercial viticulture by mitigating abiotic and biotic stresses and enhancing scion characteristics. Although Dogridge (Vitis champinii) is widely used for wine grapes, it is generally unsuitable due to its tendency to accumulate higher potassium, phenols, and tannins, along with lower acidity in berries. In this study, wine grape cultivar Syrah was evaluated on seven interspecific Vitis rootstocks, namely SO4, 110R, P1103, 140Ru, Fercal, 3309 C and 41B, to assess their influence on the vegetative, physiological, biochemical and quality traits. The experiment was conducted in a randomised block design and the data obtained were analysed using SAS software. The experiment revealed significant variations among rootstocks. Rootstock P1103 showed the earliest berry ripening, longer bunches (14.17 cm), highest total phenols (158.43 mg 100 ml-1 GAE), total flavonoids (83.5 mg 100 ml-1 QE), and yield (9.26 kg vine-1). Rootstock 110R induced the earliest budburst and produced longest internodes (10.08 cm), highest berry TSS (22.26°Brix), total monomeric anthocyanins (406 mg 100 g-1 FW) and lowest juice acidity (0.40%) along with dense trichomes- indicators of stress resistance. Rootstock 41B showed superior juice recovery (72.45%), reducing sugars (14.91%) and leaf iron content (408.93 μg g-1). Rootstock SO4 induced maximum cane length (131.89 cm), bunch weight (170.53 g), berry weight (1.487 g) and length (12.61 mm), highest leaf chlorophyll ‘a’, total chlorophyll, and P (0.235%) and Zn content (96.67 μg g-1), along with the highest peroxidase activity. These findings highlight the significant impact of rootstocks selection on Syrah performance, emphasizing the need for long-term evaluation to determine their commercial suitability.